Wear-resistant low-carbon aluminum alloy and preparation method thereof

By controlling the silicon content in aluminum alloy and adding Ce and La, combined with heat treatment technology, wear-resistant low-carbon aluminum alloy is prepared, which solves the wear problem of aluminum alloy in service environment, while maintaining high tensile strength and improving hardness and Wear resistance.

CN119491147AActive Publication Date: 2025-02-21GUANGDONG HONGBANG ALUMINUM METAL IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411692039.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

At this stage, aluminum alloys are easily worn in service environments, resulting in a reduced service life and it is difficult to maintain a high tensile strength when improving wear resistance.

Method used

By controlling the silicon content in the aluminum alloy and adding an appropriate amount of Ce and La, adjusting the addition ratio of Ce and La and the addition ratio of Mg and Mn, combining variable temperature heat treatment and vacuum microwave heat treatment, a wear-resistant low-carbon aluminum alloy is prepared.

Benefits of technology

It effectively ensures the tensile strength of aluminum alloy, while improving its hardness and wear resistance, and comprehensively improving the performance of aluminum alloy.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a wear-resistant low-carbon aluminum alloy and a preparation method thereof, and relates to the technical field of aluminum alloy preparation. The wear-resistant low-carbon aluminum alloy is composed of Si, Mg, Mn, Cu, Zr, Ti, Zn, Ce, La and Al, the mass ratio of Ce to La is 2: 1, the mass ratio of Mg to Mn is 1: 1, and in the preparation process, all the components are melted, cast, subjected to variable-temperature heat treatment, then subjected to nitrogen charging heat preservation and subjected to vacuum microwave heat treatment. The defects in the prior art are overcome, the tensile strength of the aluminum alloy is effectively guaranteed, the hardness and wear resistance of the aluminum alloy are improved on the basis, and the performance of the aluminum alloy is comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloy preparation, and in particular to a wear-resistant low-carbon aluminum alloy and a preparation method thereof. Background Art

[0002] Aluminum alloys have the characteristics of low density, good processing performance and corrosion resistance, and are widely used in aerospace, shipbuilding and machinery, etc. However, aluminum alloy structural parts are often subject to different forms of wear in the service environment, such as reciprocating sliding, erosion and wear corrosion, which greatly reduces the service life of aluminum alloy components.

[0003] At present, the hardness and wear resistance of aluminum alloy can be adjusted to a certain extent by adjusting the silicon content in aluminum alloy. Among them, the increase of silicon content can significantly improve the hardness and wear resistance of aluminum alloy, but too high silicon content will lead to a decrease in the tensile strength of aluminum alloy, which will affect the application of aluminum alloy to a certain extent. Therefore, how to improve the wear resistance of aluminum alloy while ensuring higher tensile strength is the main research direction at this stage. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a wear-resistant low-carbon aluminum alloy and a preparation method thereof, which effectively ensures the tensile strength of the aluminum alloy, and on this basis improves the hardness and wear resistance of the aluminum alloy, thereby comprehensively improving the performance of the aluminum alloy.

[0005] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:

[0006] The wear-resistant low-carbon aluminum alloy and the preparation method thereof are composed of the following raw materials in mass percentage: Si: 4%-8%, Mg: 0.8%-1.0%, Mn: 0.8%-1.0%, Cu: 1.2%-1.5%, Zr: 0.2%-0.3%, Ti: 0.1%-0.3%, Zn: 2.2%-2.6%, Ce: 0.08%-0.12%, La: 0.04%-0.06%, and the rest are Al and unavoidable impurities, and the mass ratio of Ce to La is 2:1, and the mass ratio of Mg to Mn is 1:1.

[0007] The preparation method of the wear-resistant low-carbon aluminum alloy comprises the following steps:

[0008] S1. After heating and melting the aluminum ingot, add the zinc block and the magnesium block, continue to heat up to 800-850°C after melting, add the aluminum-copper master alloy and continue to heat and melt to obtain the molten metal for use;

[0009] S2, adding aluminum silicon master alloy, aluminum manganese master alloy, aluminum zirconium master alloy, aluminum titanium master alloy, aluminum lanthanum cerium master alloy to the above molten metal, and incubating the molten metal after melting to obtain an incubated molten metal for later use;

[0010] S3, adding a refining agent to the above-mentioned inoculated metal liquid, refining and removing slag, and then analyzing the components, adjusting the content of each component to meet the standard, and then heat-insulating for 30-40 minutes to obtain the alloy liquid for standby use;

[0011] S4, casting the alloy liquid, then heat-treating it at 300-350°C for 1-2h, then cooling it to 120-150°C and continuing heat-treating it for 30-40min, then filling it with nitrogen and pressurizing it to 0.2-0.3Mpa, and heating it to 450-550°C for heat treatment for 1-2h, then restoring the pressure to normal pressure and cooling it to normal temperature to obtain an alloy blank for standby use;

[0012] S5. The alloy blank is subjected to vacuum microwave heat treatment at 350-450°C for 15-20min, then rapidly cooled to 200-250°C, heat-insulated for 40-60min, and then cooled to room temperature in a room temperature environment to obtain a wear-resistant low-carbon aluminum alloy.

[0013] Preferably, in step S1, the temperature of the zinc block and the magnesium block when they are added is controlled at 700-800° C., and the melting time of the zinc block and the magnesium block is controlled at 20-40 min.

[0014] Preferably, the temperature of adding the aluminum-copper intermediate alloy and continuing to heat and melt it in step S1 is 850-900° C., and the melting time is 15-20 min.

[0015] Preferably, the temperature of the melt incubation in step S2 is 800-850° C., and the incubation time is 40-80 min.

[0016] Preferably, in step S3, the refining agent is KCl, NaCl, CaF2, and NaF mixed in a mass ratio of 3:2:1:0.6, and the amount of the refining agent added is 0.2%-0.5% of the total mass of the inoculated metal liquid.

[0017] Preferably, the temperature of refining and deslagging in step S3 is 740-760° C., and the refining time is 40-60 min.

[0018] Preferably, in step S4, the cooling rate is 10-15°C / min, and the heating rate is 8-12°C / min.

[0019] Preferably, the rapid cooling rate in step S5 is 20-30°C / min.

[0020] The present invention provides a wear-resistant low-carbon aluminum alloy and a preparation method thereof, which has the following advantages over the prior art:

[0021] The present invention controls the silicon content in the aluminum alloy, adds a certain content of Ce and La, and controls the addition ratio of Ce and La as well as the addition ratio of Mg to Mn, which can effectively ensure the tensile strength of the aluminum alloy, and further improve the hardness and wear resistance of the alloy. The present invention subsequently combines variable temperature heat treatment and vacuum microwave heat treatment to effectively treat the alloy surface, comprehensively improve the hardness and wear resistance of the alloy surface, and enhance the application effect of the alloy. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The refining agent used in the following examples and comparative examples has the following mass ratio material composition: KCl: NaCl: CaF2: NaF is mixed in a mass ratio of 3: 2: 1: 0.6.

[0024] Embodiment 1:

[0025] Preparation of aluminum alloy:

[0026] (1) After heating the aluminum ingot to 700°C and melting it, zinc and magnesium blocks are added and the melting process is continued for 30 minutes. After that, the temperature is raised to 800°C, aluminum-copper master alloy is added and the temperature is further raised to 850°C and melted for 20 minutes to obtain molten metal for use;

[0027] (2) adding aluminum silicon master alloy, aluminum manganese master alloy, aluminum zirconium master alloy, aluminum titanium master alloy, and aluminum lanthanum cerium master alloy to the above molten metal, melting at 800° C. and incubating for 80 minutes to obtain an inoculated molten metal for later use;

[0028] (3) Add 0.2% of the total mass of the inoculant metal to the inoculant metal, and perform refining and slag removal at 740° C. for 60 min. After component analysis, adjust the mass percentage of each component as follows:

[0029] Si: 4%, Mg: 0.8%, Mn: 0.8%, Cu: 1.2%, Zr: 0.2%, Ti: 0.1%, Zn: 2.2%, Ce: 0.08%, La: 0.04%, the rest is Al and unavoidable impurities;

[0030] After the heat preservation treatment for 40 minutes, the alloy liquid is ready for use;

[0031] (4) casting the alloy liquid, then heat-treating at 300°C for 2h, then cooling to 120°C at a rate of 10°C / min and continuing heat-treating for 40min, then heating to 450°C at a rate of 8°C / min, increasing the pressure to 0.2Mpa, and performing nitrogen protection heat treatment for 2h, then returning to normal pressure and cooling to room temperature to obtain an alloy blank for standby use;

[0032] (5) The alloy blank was subjected to vacuum microwave heat treatment at 350°C for 20 min, then rapidly cooled to 200°C at a rate of 20°C / min, kept at this temperature for 60 min, and then cooled to room temperature in a room temperature environment to obtain a wear-resistant low-carbon aluminum alloy.

[0033] Embodiment 2:

[0034] Preparation of aluminum alloy:

[0035] (1) After heating the aluminum ingot to 800°C and melting it, zinc and magnesium blocks are added and the melting process is continued for 20 minutes. After heating to 850°C, aluminum-copper master alloy is added and the temperature is continued to be raised to 900°C and melted for 15 minutes to obtain molten metal for use;

[0036] (2) adding aluminum silicon master alloy, aluminum manganese master alloy, aluminum zirconium master alloy, aluminum titanium master alloy, and aluminum lanthanum cerium master alloy to the above molten metal, melting at 850° C. and incubating for 40 minutes to obtain an inoculated molten metal for later use;

[0037] (3) Add 0.5% of the total mass of the inoculant metal to the inoculant metal, and perform refining and slag removal at 760° C. for 40 min. After component analysis, adjust the mass percentage of each component as follows:

[0038] Si: 8%, Mg: 1.0%, Mn: 1.0%, Cu: 1.5%, Zr: 0.3%, Ti: 0.3%, Zn: 2.6%, Ce: 0.12%, La: 0.06%, the rest is Al and unavoidable impurities;

[0039] After the heat preservation treatment for 30 minutes, the alloy liquid is ready for use;

[0040] (4) casting the alloy liquid, then heat-treating at 350°C for 1 hour, then cooling to 150°C at a rate of 15°C / min and continuing heat-treating for 30 minutes, then heating to 550°C at a rate of 12°C / min, increasing the pressure to 0.3 MPa, performing nitrogen protection heat treatment for 1 hour, then returning to normal pressure and cooling to room temperature to obtain an alloy blank for standby use;

[0041] (5) The alloy blank was subjected to vacuum microwave heat treatment at 450°C for 15 min, then rapidly cooled to 250°C at a rate of 30°C / min, kept at this temperature for 40 min, and then cooled to room temperature in a room temperature environment to obtain a wear-resistant low-carbon aluminum alloy.

[0042] Comparative Example 1:

[0043] Referring to the preparation method of Example 1 above, only the mass percentage of each component in step (3) is adjusted as follows:

[0044] Si: 4%, Mg: 0.8%, Mn: 1.0%, Cu: 1.2%, Zr: 0.2%, Ti: 0.1%, Zn: 2.2%, Ce: 0.12%, La: 0.04%, and the rest are Al and inevitable impurities.

[0045] Comparative Example 2:

[0046] Referring to the preparation method of Example 1 above, only the mass percentage of each component in step (3) is adjusted as follows:

[0047] Si: 4%, Mg: 1.0%, Mn: 0.8%, Cu: 1.2%, Zr: 0.2%, Ti: 0.1%, Zn: 2.2%, Ce: 0.08%, La: 0.06%, and the rest are Al and inevitable impurities.

[0048] Comparative Example 3:

[0049] Preparation of aluminum alloy:

[0050] Steps (1) to (3) are the same as in Example 1;

[0051] (4) casting the alloy liquid, then heat-treating at 300°C for 2h, then cooling to 120°C at a rate of 10°C / min and continuing heat-treating for 40min, then heating to 450°C at a rate of 8°C / min, heat-treating for 2h, then returning to normal pressure and cooling to room temperature to obtain an alloy blank for standby use;

[0052] (5) The alloy blank was subjected to vacuum microwave heat treatment at 350°C for 20 min, then rapidly cooled to 200°C at a rate of 20°C / min, kept at this temperature for 60 min, and then cooled to room temperature in a room temperature environment to obtain a wear-resistant low-carbon aluminum alloy.

[0053] Comparative Example 4:

[0054] Preparation of aluminum alloy:

[0055] Steps (1) to (3) are the same as in Example 1;

[0056] (4) The alloy liquid is cast and then heat-treated at 300°C for 2 h, then cooled to 120°C at a rate of 10°C / min and heat-treated for 40 min, then heated to 450°C at a rate of 8°C / min, and pressurized to 0.2 MPa, heat-treated for 2 h with nitrogen protection, then restored to normal pressure and cooled to room temperature to obtain a wear-resistant low-carbon aluminum alloy.

[0057] Detection:

[0058] 1. The tensile strength, yield strength and elongation of aluminum alloy castings tested in accordance with GB / T 228.1-2010 Tensile Tests for Metallic Materials Part 1: Test Methods at Room Temperature (tensile speed: 2 mm / min) were measured. According to the standard: GB / T231.1-2009, three points were tested and the average value was taken to obtain the Vickers hardness of each group of materials. The mechanical properties of the die-cast aluminum alloys prepared in the above Examples 1-2 and Comparative Examples 1-4 were tested. The specific results are shown in Table 1 below:

[0059] Table 1

[0060] Group Yield Strength(Mpa) Tensile strength(Mpa) Elongation(%) Example 1 329Mpa 462MPa 4.53% Example 2 331Mpa 463Mpa 4.52% Comparative Example 1 306Mpa 415Mpa 4.57% Comparative Example 2 293Mpa 402Mpa 4.62% Comparative Example 3 296Mpa 405Mpa 4.55% Comparative Example 4 301Mpa 410Mpa 4.56%

[0061] 2. The Vickers hardness (3 points were tested according to GB / T231.1-2009 and the average value was taken) and the wear rate (each group of aluminum alloys was subjected to a sliding friction and wear test under the test conditions of a constant speed of 400 rpm and a constant load of 7 N to detect the wear rate) of the aluminum alloys prepared in Examples 1-2 and Comparative Examples 1-4. The specific results are shown in Table 2 below:

[0062] Table 2

[0063] Group <![CDATA[Vickers hardness (HV, kg / mm 2 )]]> Wear rate (g / N·m) Example 1 624 3.9 Example 2 625 3.8 Comparative Example 1 593 4.5 Comparative Example 2 602 4.4 Comparative Example 3 610 4.2 Comparative Example 4 608 4.6

[0064] From the above tests, it can be seen that Example 1-2 has higher mechanical properties and higher hardness, and lower wear rate, and can achieve wear-resistant effect.

[0065] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. Wear-resistant low-carbon aluminum alloy, characterized in that: The wear-resistant low-carbon aluminum alloy and its preparation method are composed of the following raw materials in percentage by mass: Composition: Si: 4%-8%, Mg: 0.8%-1.0%, Mn: 0.8%-1.0%, Cu: 1.2%-1.5%, Zr: 0.2%-0.3%, Ti: 0.1%-0.3%, Zn: 2.2%-2.6%, Ce: 0.08%-0.12%, La: 0.04%-0.06%, and the rest are Al and unavoidable impurities, and the mass ratio of Ce to La is 2:1, and the mass ratio of Mg to Mn is 1:

1.

2. A method for preparing a wear-resistant low-carbon aluminum alloy as claimed in claim 1, characterized in that: The preparation method comprises the following steps: S1. After heating and melting the aluminum ingot, add the zinc block and the magnesium block, continue to heat up to 800-850°C after melting, add the aluminum-copper master alloy and continue to heat and melt to obtain the molten metal for use; S2, adding aluminum silicon master alloy, aluminum manganese master alloy, aluminum zirconium master alloy, aluminum titanium master alloy, aluminum lanthanum cerium master alloy to the above molten metal, and incubating the molten metal after melting to obtain an incubated molten metal for later use; S3, adding a refining agent to the above-mentioned inoculated metal liquid, refining and removing slag, and then analyzing the components, adjusting the content of each component to meet the standard, and then heat-insulating for 30-40 minutes to obtain the alloy liquid for standby use; S4, casting the alloy liquid, then heat-treating it at 300-350°C for 1-2h, then cooling it to 120-150°C and continuing heat-treating it for 30-40min, then filling it with nitrogen and pressurizing it to 0.2-0.3Mpa, and heating it to 450-550°C for heat treatment for 1-2h, then restoring the pressure to normal pressure and cooling it to normal temperature to obtain an alloy blank for standby use; S5. The alloy blank is subjected to vacuum microwave heat treatment at 350-450°C for 15-20min, then rapidly cooled to 200-250°C, heat-insulated for 40-60min, and then cooled to room temperature in a room temperature environment to obtain a wear-resistant low-carbon aluminum alloy.

3. The preparation method according to claim 2, characterized in that: In the step S1, the temperature of the zinc block and the magnesium block when they are added is controlled at 700-800° C., and the melting time of the zinc block and the magnesium block is controlled at 20-40 minutes.

4. The preparation method according to claim 2, characterized in that: The temperature of adding the aluminum-copper master alloy and continuing to heat up and melt in step S1 is 850-900° C., and the melting time is 15-20 minutes.

5. The preparation method according to claim 2, characterized in that: The temperature of the melt incubation in step S2 is 800-850° C., and the incubation time is 40-80 min.

6. The preparation method according to claim 2, characterized in that: In step S3, the refining agent is KCl, NaCl, CaF2, and NaF mixed in a mass ratio of 3:2:1:0.6, and the amount of the refining agent added is 0.2%-0.5% of the total mass of the inoculated metal liquid.

7. The preparation method according to claim 2, characterized in that: The temperature of refining and deslagging in step S3 is 740-760° C., and the refining time is 40-60 min.

8. The preparation method according to claim 2, characterized in that: In step S4, the cooling rate is 10-15°C / min, and the heating rate is 8-12°C / min.

9. The preparation method according to claim 2, characterized in that: The rapid cooling rate in step S5 is 20-30°C / min.

Citation Information

Patent Citations

  • Heat-treatment-free die-casting aluminum alloy and preparation method thereof

    CN115852213A

  • Explosion-proof and explosion-proof aluminum alloy material and preparation method thereof

    CN117646138A

  • Low-cost heat-treatment-free high-toughness die-casting aluminum alloy and preparation method thereof

    CN117987697A

  • Heat-treatment-free aluminum alloy material as well as preparation method and application thereof

    CN118497565A

  • Oil pump made of aluminum alloys

    EP0577062A1